An Overview of Company Valuation: Looking at the Environmental, Social and Governance (ESG) Disclosure Dimension Studies - Nita Rahman; Agus Satrya Wibowo; Ricky Yunisar Setiawan; Tatik Zulaika (Jurnal Akuntansi, 2025)
A fundamental to increasing firm value and attracting investors is preserving long-term corporate sustainability through the implementation of sound corporate governance standards that take ESG concerns into consideration. This study examines the potential impact of governance, social, and environmental disclosures on firm value. Businesses in the infrastructure sector that were listed on the IDX between 2021 and 2023 were used as the population and samples. Purposive sampling was used, and SmartPLS Version 4 software was used for testing. Both the inner and outer models are used in the data analysis method. The findings indicate that only governance disclosure, not environmental or social disclosure, has an impact on firm value. This study builds o$n earlier research that emphasizes the significance of ESG data in influencing investment choices and optimizing firm value. It also gives businesses advice on how to incoordinate ESG considerations into their operatios.